Prevalence and Correlates of Anxiety and Depressive Symptoms in Patients With and Without Multi-Drug Resistant Pulmonary Tuberculosis in China - Liu, Kewei; Zhang, Yidan; Qu, Shilin; Yang, Wenying; Guo, Liyuan; Zhang, Liqun (Frontiers in Psychiatry, 2021)
China is still among the 30 high-burden tuberculosis (TB) countries in the world and TB remains a public health concern. TB can be a cause of mental illness, with prolonged treatment and several anti-TB drugs leading to extreme mental health problems such as depression and anxiety in TB patients. To investigate the prevalence of anxiety and depressive symptoms among TB patients, and to explore whether drug resistance is a covariate for depressive and anxiety symptoms, a total of 167 pulmonary tuberculosis patients were enrolled in this study, which was conducted from January 1 to September 30, 2020. Data were collected, using a structured questionnaire with a demographic component, the Hospital Anxiety and Depression Scale (HADS), General Health Questionnaire 20 (GHQ-20), the Tuberculosis-related Stigma Scale (TSS) and the Social Support Rating Scale (SSRS). Association between demographics, disease/treatment characteristics, stigma, social support, and anxiety/depression symptoms were investigated either based on Pearson’s correlation coefficient or group comparisons based on independent t-test (or Mann-Whitney U test) Multiple linear stepwise regression analysis was used for determining the predictors of anxiety and depression. The results showed that multi-drug resistance pulmonary tuberculosis patients were associated with anxiety challenges. Multiple linear regression analysis indicated that self-esteem accounted for 33.5% and 38% of the variation in anxiety and depression, respectively. This shows that among tuberculosis patients, self-esteem is the factor that could most explains the depression and anxiety symptoms of patients, suggesting that we may could through improving the environment, society, and family respect and tolerance of tuberculosis patients, thereby improving the mental health of tuberculosis patients.